Global Cities – Cities Changed Social-Cultural Space; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Matveeva O. Yu. Olga Yurjevna (2017, 2017)
Title screen